Analysis of Conditions and Problems of Pre-Departure Training for Caregiver Candidate Internships in Indonesia - Novita Rozaliana Fadillah, Andi; Fahrul Rochim, Julita (Journal of World Science, 2023)
Within a decade, starting in 2008, the Japanese government opened up the acceptance of foreign workers in the caregiver field, and Indonesia is one of the countries with the most significant number of senders of caregivers in Japan. There are at least four routes for sending caregivers to Japan, one of which is through sending caregiver interns "Kaigo Ginou Jisshuu." This study analyzes the conditions and problems of pre-departure training for caregiver intern candidates in Indonesia. The method used in this study is qualitative and quantitative. Data collection techniques used were interviews, observations, and questionnaires. This study used a purposive sampling technique. The "Ginou Jisshuu" program, through the case study of Nagomi Kaigo Gakkou, can be described that most teachers at LPK are interns with quite high Japanese language skills and experience living in Japan, where this becomes potential in teaching Japanese to prospective interns. The results of this research can become a reference for higher education institutions in community service activities, especially in improving Japanese language teaching in LPK.